Regulating State Use of Force: A Critical Assessment of International Human Rights Protections and Enforcement Challenges - Dr. Nadia Zafar; Dr. Muhammad Saqlain Haider; Muhammad Bilal; Muhammad Musab Umair Ul Hassan (ACADEMIA International Journal for Social Sciences, 2025)
The regulation of force by state authorities is a complex area of international human rights law, balancing state sovereignty, public security, and human dignity. This paper examines the legal framework governing law enforcement and security agencies, focusing on principles of legality, necessity, proportionality, precaution, and accountability as articulated in instruments such as the UN Code of Conduct for Law Enforcement Officials (1979), the UN Basic Principles on the Use of Force and Firearms (1990), and the right to life provisions of the UDHR, ICCPR, and General Comment No. 36. Leading jurisprudence from the European Court of Human Rights and the Inter-American Court of Human Rights including McCann and Others v United Kingdom, Nachova and Others v Bulgaria, Makaratzis v Greece, Armani Da Silva v United Kingdom, and Nadege Dorzema et al v Dominican Republic alongside domestic cases such as Tennessee v Garner, illustrates how these standards are applied, emphasizing operational planning, non-discrimination, effective investigation, and institutional accountability. Empirical research and reports by Amnesty International, Human Rights Watch, and the Council of Europe, complemented by academic analyses, reveal persistent gaps in practice, including inadequate training, weak oversight, discriminatory policing, militarization, and challenges in protest management. The paper concludes that while international human rights law provides a robust normative framework, structural, political, and cultural barriers continue to impede effective regulation, highlighting the need for strengthened accountability and comprehensive institutional reform.